Pattern of orbital exenteration at a tertiary eye care centre in North India - Kaur, A; Khattri, M; Jaiswal, V (Nepalese Journal of Ophthalmology, 2012)
Objective: To analyze cases undergoing orbital exenteration in terms of demographic and socioeconomic profile of patients, indications for surgery, histopathological diagnosis and to assess the magnitude of eyelid malignancies as indication of orbital exenteration. Materials and methods: A case record analysis of 25 patients who underwent orbital exenteration at a tertiary care centre in India between October 2002 and October 2007 was undertaken. The case records were reviewed to obtain demographic data, presenting symptoms, duration of symptoms, laterality, best-corrected visual acuity (BCVA), and the clinical and histopathological diagnosis. Results: The age group of patients undergoing exenteration ranged from 1 year to 78 years (Mean 46.92 ± 10 years). Proptosis and/or a palpable mass were the main presenting complaints in 80 % of cases. The duration of symptoms was more than 5 years in 80 % cases. Primary orbital malignancies were the commonest indication for exenteration and were diagnosed in 11cases (44 %), followed by lid malignancies in 8 cases (32 %), retinoblastoma in 4 cases (16 %) and conjunctival malignancies in 2 cases (8 %). Sebaceous gland carcinoma was the commonest lid malignancy followed by basal cell carcinoma and squamous cell carcinoma. Conclusion: Lid malignancies contribute the majority of the patients undergoing orbital exenteration in this part of the world, leading to an extreme sacrifice of eyes with good visual acuity. Increase in awareness, early diagnosis and prompt referral may help to overcome this grim scenario. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5853 NEPJOPH 2012; 4(1): 64-67